AI-Driven Proactive Monitoring: Mitigating Agency Costs and Financial Risk - Raden Agrosamdhyo (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Background: In the domain of corporate governance, the separation of ownership and control generates significant agency conflicts, primarily manifesting as Earnings Management (EM). Traditional reactive auditing methods fail to detect manipulation concealed within unstructured data, leading to high agency costs and diminished stakeholder trust. Objective: This study proposes an